A comparison of HMGB1 concentrations between cerebrospinal fluid and blood in patients with neurological disease. (3rd October 2017) - Walker, Lauren Elizabeth; Griffiths, Michael John; McGill, Fiona; Lewthwaite, Penelope; Sills, Graeme John; Jorgensen, Andrea; Antoine, Daniel James; Solomon, Tom; Marson, Anthony Guy; Pirmohamed, Munir
Abstract: Aims: To determine whether a correlation exists between paired cerebrospinal fluid (CSF) and serum levels of a novel inflammatory biomarker, high-mobility group box 1 (HMGB1), in different neurological conditions. Methods: HMGB1 was measured in the serum and CSF of 46 neurological patients (18 idiopathic intracranial hypertension [IIH], 18 neurological infection/inflammation [NII] and 10 Rasmussen's encephalitis [RE]). Results: Mean serum (± SD) HMGB1 levels were 1.43 ± 0.54, 25.28 ± 27.9 and 1.89 ± 1.49 ng/ml for the patients with IIH, NII and RE, respectively. Corresponding mean (± SD) CSF levels were 0.35 ± 0.22, 4.48 ± 6.56 and 2.24 ± 2.35 ng/ml. Both CSF and serum HMGB1 was elevated in NII. Elevated CSF HMGB1 was demonstrated in RE. There was no direct correlation between CSF and serum levels of HMGB1. Conclusion: Serum HMGB1 cannot be used as a surrogate measure for CSF levels. CSF HMGB1 was elevated in NII and RE, its role as a prognostic/stratification biomarker needs further study.